Waterproof nylon fabric and preparation method thereof
Waterproof nylon fabric is prepared by polymerization reaction of modified diamine and dicarboxylic acid and melt blending with double-bond terminated polyurethane prepolymer, which solves the problem of decreased waterproof performance and poor breathability of nylon fabric after washing and achieves a balance between high waterproofness and breathability.
Patent Information
- Application Number
- CN202510867687.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-26
- Publication Date
- 2025-09-16
AI Technical Summary
Existing nylon fabrics have reduced waterproof performance and poor breathability after washing, making it difficult to simultaneously meet the requirements of high waterproofness and breathability.
Waterproof nylon fabric is prepared through the polymerization reaction of modified diamine and dicarboxylic acid, combined with the melt blending of double-bond terminated polyurethane prepolymer, and the waterproof and breathable properties are improved by covalent condensation and graft copolymerization.
The waterproof and breathable properties of nylon fabrics are improved, and the washability is good, avoiding the problem of decreased breathability caused by traditional waterproofing agent coating.
Smart Images

Figure BDA0005469035530000171 
Figure BDA0005469035530000181
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nylon preparation, and particularly relates to a waterproof nylon fabric and a preparation method thereof. Background Art
[0002] Nylon, also known as polyamide fiber or nylon, is a chemically synthesized fiber belonging to the polyamide family. It is a thermoplastic resin containing repeating amide groups, primarily derived through the condensation polymerization of dibasic acids and diamines or the ring-opening polymerization of lactams. Nylon is a highly polar polymer material that forms numerous hydrogen bonds between its molecules, resulting in excellent mechanical properties, hydrophilicity, lubricity, and wear resistance. It is non-toxic, odorless, and has excellent processability. Nylon has been widely used in many fields due to its excellent physical and chemical properties. Its main uses include: (1) Clothing fabrics: Nylon is widely used in sportswear, windbreakers, jackets, swimsuits, etc. due to its lightness, wear resistance and wrinkle resistance; (2) Industrial applications: Nylon is increasingly used in the automotive, aerospace, electronic equipment and mechanical parts fields, especially in parts that require light weight and high strength; (3) Household items: Nylon carpets, curtains and furniture decorations are popular due to their durability and easy cleaning; (4) Medical devices: Nylon is used in medical devices such as sutures and catheters due to its biocompatibility and excellent mechanical properties.
[0003] Nylon is widely used in clothing fabric applications due to its unique properties. However, with the popularity of outdoor activities and sports, consumers have increasingly demanded higher performance from clothing materials, especially waterproof performance. As a lightweight and wear-resistant fabric, nylon has certain waterproof properties, but it is not completely waterproof. This is mainly because although nylon has a low moisture regain and has certain waterproof properties, its structure contains a large number of polar hydrophilic amide bonds. If exposed to water for a long time (such as outdoor activities such as hiking and mountaineering that are prone to rain contact) or soaked in water (for washing), the nylon will absorb moisture, thereby reducing its durability. In the face of these situations, the waterproofness of nylon fabrics needs to be further improved.
[0004] Patent CN117551344A discloses a low-moisture absorption nylon material and its preparation method. The invention uses nylon resin, antioxidant, dispersant, modified epoxy resin and modified disulfide nanosheets as raw materials. First, the inorganic filler tungsten disulfide is modified by introducing amino groups on its surface. The amino groups can interact with the amide bonds in the nylon, hindering the interaction between water molecules and the amide bonds in the nylon molecules, thereby reducing the water absorption of the nylon material and improving wear resistance. Secondly, the epoxy resin is hydrophobic and flame retardant modified. Nitrogen and boron flame retardants are grafted onto the side chains of the epoxy resin, and fluorine atoms are introduced into the main chain structure, thereby improving the overall flame retardancy and hydrophobicity of the nylon material.
[0005] Prior art also uses processes such as padding with waterproofing agents to enhance fabric waterproofing, such as using fluorine-containing waterproofing agents to waterproof fabrics. However, due to the polluting and toxicity of fluorine-containing waterproofing agents, their use has been gradually restricted. Fluorine-free waterproofing agents, including silicone-based fluorine-free waterproofing agents, fluorine-free water-based polyurethane waterproofing agents, acrylate-based fluorine-free water repellents, and modified amino resin waterproofing agents, offer excellent environmental and waterproof properties, but they exhibit poor washability, with waterproofing properties decreasing after washing. Furthermore, the high film density of these waterproofing agents can lead to poor air permeability in fabrics.
[0006] Therefore, it is of great significance to improve the breathability of nylon fabric while maintaining good waterproof performance after washing. Summary of the Invention
[0007] To address the shortcomings of the prior art, the present invention involves polymerizing a prepared modified diamine mixture and a dicarboxylic acid mixture to produce modified nylon, which is then melt-blended with a double-bond-terminated polyurethane prepolymer to produce a waterproof nylon fabric. Through cross-linking polymerization, the waterproof and breathable properties of the waterproof nylon fabric are enhanced, thereby resolving the technical problems identified in the prior art. Specifically, the present invention comprises the following technical solutions:
[0008] One of the purposes of the present invention is to provide a method for preparing a waterproof nylon fabric, the preparation method comprising the following steps:
[0009] The dicarboxylic acid mixture and the modified diamine mixture are mixed and dispersed in a weight ratio of 1:1-2, and the pH is adjusted to 7.0-7.5, and then heated to 80-90°C for a reaction time of 90-110 minutes to obtain a nylon salt solution;
[0010] The nylon salt solution and the antioxidant are mixed in a weight ratio of 1:0.008-0.01, and the mixture is heated to 200° C.-220° C. under nitrogen atmosphere and reacted for 2 h-3 h to obtain a nylon prepolymer;
[0011] The nylon prepolymer is dried at 70°C to 80°C for 6h to 10h, then vacuumed to 8Pa to 10Pa, and then heated to 230°C to 240°C for 18h to 20h to obtain modified nylon;
[0012] The modified nylon and the double-bond terminated polyurethane prepolymer are mixed in an extruder in a weight ratio of 5-8:2-3, and are melt-blended at a speed of 50-80 r / min and a temperature of 200-210° C. for 6-9 minutes to obtain a waterproof nylon fabric.
[0013] Furthermore, the dicarboxylic acid mixture is composed of benzene ring-containing dicarboxylic acid, olefin dicarboxylic acid and anhydrous ethanol in a weight ratio of 1:3-5:8-12.
[0014] Furthermore, the benzene ring-containing dicarboxylic acid includes 1,4-benzenedicarboxylic acid or 1,4-benzenedicarboxylic acid.
[0015] Furthermore, the olefinic dicarboxylic acid includes maleic acid.
[0016] Furthermore, the preparation method of the modified diamine mixed solution comprises the following steps:
[0017] A silane coupling agent, a terminal hydroxyl aldehyde compound and a mixed solvent are mixed in a weight ratio of 1:3 to 6:10 to 20, and the pH is adjusted to 4 to 4.5. The mixture is then heated to 60° C. to 70° C. and reacted for 2 to 3 hours to obtain a modified silane coupling agent.
[0018] The modified silane coupling agent and the diamine compound are mixed in a weight ratio of 1:2-3, and then stirred and reacted in an environment of 25-30° C. for 12-15 hours to obtain a modified diamine mixed solution.
[0019] Furthermore, the silane coupling agent includes silane coupling agent KH-792, which must contain amino groups in its structure to supplement the amino groups consumed by the subsequent modified silane coupling agent through the reaction between the aldehyde groups in its own structure and the amino groups on the diamine compound, so as to facilitate subsequent participation in the polymerization reaction.
[0020] Furthermore, the terminal hydroxyl aldehyde compound includes hydroxycitronellal, which has a hydroxyl group at one end and an aldehyde group at the other end in its structure. The role of the hydroxyl group is to condense with the silane coupling agent after hydrolysis to form a siloxane structure to obtain a modified silane coupling agent, and the role of the aldehyde group is to form an imine bond with the amino group on the diamine compound, which can not only achieve connection to the diamine compound to obtain a modified diamine, but also increase the formation of high-temperature resistant imine bonds in the structure.
[0021] Furthermore, the mixed solvent is obtained by mixing anhydrous ethanol and deionized water in a weight ratio of 1:1.
[0022] Furthermore, the diamine compound includes 1,5-pentanediamine or 1,6-hexanediamine.
[0023] Furthermore, the antioxidant includes antioxidant 1076, antioxidant 246 or antioxidant 264.
[0024] Furthermore, the preparation method of the double-bond terminated polyurethane prepolymer comprises the following steps:
[0025] Hexamethylene diisocyanate, polycaprolactone diol and dibutyltin dilaurate are mixed and heated to 80°C to 90°C for reaction for 1h to 2h, then cooled to 50°C to 60°C and a hydroxyl compound containing a double bond is added, and the mixture is heated to 70°C to 80°C and reacted for 3h to 4h to obtain a double-bond terminated polyurethane prepolymer.
[0026] Furthermore, the number average molecular weight of the polycaprolactone diol is 2000.
[0027] Furthermore, the double bond hydroxy compound includes hydroxyethyl methacrylate or hydroxyethyl acrylate.
[0028] Furthermore, the weight ratio of hexamethylene diisocyanate: polycaprolactone diol: dibutyltin dilaurate: hydroxy compound containing a double bond is 8-11: 6-7: 0.015-0.04: 1-4.
[0029] A second object of the present invention is to provide a waterproof nylon fabric prepared by the method for preparing the waterproof nylon fabric.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention modifies the diamine compound required for nylon preparation at the initial stage of nylon preparation. First, a silane coupling agent containing a relatively long carbon chain and having a terminal amino group and a terminal hydroxyl-aldehyde compound having terminal hydroxyl groups and terminal aldehyde groups are reacted to form a covalent condensed siloxane bond structure between the silanol groups and the hydroxyl groups, thereby providing the prepared modified silane coupling agent with aldehyde and amino groups. Subsequently, the diamine compound and the modified silane coupling agent are mixed and reacted, and the amino groups on the diamine compound and the aldehyde groups on the modified silane coupling agent are covalently condensed to form a high-temperature-resistant imine bond, thereby obtaining a modified diamine mixed solution. Thus, an organosilicon structure with good hydrophobicity is introduced into the monomer required for nylon preparation by covalent bonding. During the subsequent polymerization to prepare the modified nylon, the organosilicon structure is chemically bonded to the interior of the nylon, thereby improving water-washing resistance. Because covalent condensation consumes the amino groups in the diamine compound structure, if the silane coupling agent used does not have amino groups, the resulting modified diamine mixture will be unable to participate in the subsequent reaction to prepare the nylon salt solution due to the lack of amino groups. Subsequently, a polymerization reaction is carried out between a dicarboxylic acid mixture composed of a benzene ring-containing dicarboxylic acid and an olefinic dicarboxylic acid and a modified diamine mixture to obtain modified nylon. The modified nylon is then melt-blended with a double-bond-terminated polyurethane prepolymer to produce a waterproof nylon fabric. The role of the olefinic dicarboxylic acid is to subsequently graft the hydrophobic double-bond-terminated polyurethane prepolymer onto the modified nylon through graft copolymerization between unsaturated carbon-carbon double bonds, further enhancing the waterproofness of the resulting waterproof nylon fabric. This cross-linking polymerization method not only improves the waterproof performance of the waterproof nylon fabric, but also enhances its breathability, reducing the disadvantage of directly applying the waterproofing agent to the nylon fabric, which results in poor waterproofness due to the high film density. DETAILED DESCRIPTION
[0032] The following will clearly and completely describe the technical solutions of the present invention through the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making any creative efforts shall fall within the scope of protection of the present invention.
[0033] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.
[0034] Preparation Example 1:
[0035] The preparation method of the modified diamine mixed solution specifically includes the following steps:
[0036] 2 parts by weight of silane coupling agent KH-792 and 20 parts by weight of a mixed solvent (anhydrous ethanol and deionized water in a 1:1 ratio by weight) were mixed and stirred until uniformly dispersed. 6 parts by weight of hydroxycitronellal were then added and continued to mix and stir to obtain a mixture. The pH of the mixture was then adjusted to 4 with dilute hydrochloric acid. The adjusted mixture was then placed at 60°C and stirred at 200 r / min for 2 hours. After the reaction, the mixed solvent was removed by evaporation under reduced pressure to obtain a modified silane coupling agent. 1 part by weight of the modified silane coupling agent and 2 parts by weight of 1,5-pentanediamine were added to 10 parts by weight of anhydrous acetone. The mixture was then stirred at 25°C at 200 r / min for 12 hours. After the reaction, the anhydrous acetone was removed by evaporation under reduced pressure to obtain a modified diamine mixture.
[0037] Preparation Example 2:
[0038] The preparation method of the modified diamine mixed solution specifically includes the following steps:
[0039] 2 parts by weight of silane coupling agent KH-792 and 28 parts by weight of a mixed solvent (anhydrous ethanol and deionized water in a 1:1 ratio by weight) were mixed and stirred until uniformly dispersed. 8 parts by weight of hydroxycitronellal was then added and continued to mix and stir to obtain a mixture. The pH of the mixture was then adjusted to 4 with dilute hydrochloric acid. The adjusted mixture was then placed at 65°C and stirred at 200 r / min for 2.5 hours. After the reaction, the mixed solvent was removed by evaporation under reduced pressure to obtain a modified silane coupling agent. 1 part by weight of the modified silane coupling agent and 2.4 parts by weight of 1,5-pentanediamine were added to 10 parts by weight of anhydrous acetone. The mixture was then stirred at 25°C at 200 r / min for 13 hours. After the reaction, the anhydrous acetone was evaporated under reduced pressure to obtain a modified diamine mixture.
[0040] Preparation Example 3:
[0041] The preparation method of the modified diamine mixed solution specifically includes the following steps:
[0042] 2 parts by weight of silane coupling agent KH-792 and 32 parts by weight of a mixed solvent (anhydrous ethanol and deionized water in a 1:1 weight ratio) were mixed and stirred until uniformly dispersed. 10 parts by weight of hydroxycitronellal was then added and continued to mix and stir to obtain a mixture. The pH of the mixture was then adjusted to 4.5 with dilute hydrochloric acid. The adjusted mixture was then placed at 65°C and stirred at 200 r / min for 3 hours. After the reaction, the mixed solvent was removed by evaporation under reduced pressure to obtain a modified silane coupling agent. 1 part by weight of the modified silane coupling agent and 2.8 parts by weight of 1,6-hexanediamine were added to 10 parts by weight of anhydrous acetone. The mixture was then stirred at 30°C at 200 r / min for 14 hours. After the reaction, the anhydrous acetone was removed by evaporation under reduced pressure to obtain a modified diamine mixture.
[0043] Preparation Example 4:
[0044] The preparation method of the modified diamine mixed solution specifically includes the following steps:
[0045] 2 parts by weight of silane coupling agent KH-792 and 40 parts by weight of a mixed solvent (anhydrous ethanol and deionized water in a 1:1 weight ratio) were mixed and stirred until uniformly dispersed. 12 parts by weight of hydroxycitronellal was then added and continued to mix and stir to obtain a mixture. The pH of the mixture was then adjusted to 4.5 with dilute hydrochloric acid. The adjusted mixture was then placed at 70°C and stirred at 200 r / min for 3 hours. After the reaction, the mixed solvent was removed by evaporation under reduced pressure to obtain a modified silane coupling agent. 1 part by weight of the modified silane coupling agent and 3 parts by weight of 1,6-hexanediamine were added to 10 parts by weight of anhydrous acetone. The mixture was then stirred at 30°C at 200 r / min for 15 hours. After the reaction, the anhydrous acetone was removed by evaporation under reduced pressure to obtain a modified diamine mixture.
[0046] Preparation Example 5:
[0047] The preparation method of the modified diamine mixed solution specifically includes the following steps:
[0048] The silane coupling agent KH-792 in Preparation Example 4 was replaced with 3-aminopropyltrimethoxysilane, and the rest of the preparation process was consistent with Preparation Example 4.
[0049] Preparation Example 6:
[0050] The preparation method of the modified diamine mixed solution specifically includes the following steps:
[0051] The silane coupling agent KH-792 in Preparation Example 4 was replaced with silane coupling agent KH-560, and the rest of the preparation process was consistent with Preparation Example 4.
[0052] Preparation Example 7:
[0053] The preparation method of the modified diamine mixed solution specifically includes the following steps:
[0054] The hydroxycitronellal in Preparation Example 4 was replaced by glyceraldehyde, and the rest of the preparation process remained the same as that of Preparation Example 4.
[0055] Preparation Example 8:
[0056] The preparation method of the modified diamine mixed solution specifically includes the following steps:
[0057] The hydroxycitronellal in Preparation Example 4 was replaced by adipic acid, and the rest of the preparation process was consistent with Preparation Example 4.
[0058] Preparation Example 9:
[0059] The preparation method of the modified diamine mixed solution specifically includes the following steps:
[0060] The 1,6-hexanediamine in Preparation Example 4 was replaced by 1,3-propylenediamine, and the rest of the preparation process was consistent with Preparation Example 4.
[0061] Preparation Example 10:
[0062] The preparation method of the modified diamine mixed solution specifically includes the following steps:
[0063] The 1,6-hexanediamine in Preparation Example 4 was replaced by 1,10-decanediamine, and the rest of the preparation process was consistent with Preparation Example 4.
[0064] Preparation Example 11:
[0065] The preparation method of the double-bond terminated polyurethane prepolymer specifically includes the following steps:
[0066] After vacuum drying and dehydration of hexamethylene diisocyanate and polycaprolactone diol (number-average molecular weight of 2000), 8 parts by weight of the dried hexamethylene diisocyanate, 6 parts by weight of the dried polycaprolactone diol (number-average molecular weight of 2000), and 0.015 parts by weight of dibutyltin dilaurate were weighed and mixed in a reactor. Under nitrogen protection, the temperature was raised to 80°C and the reaction was timed for 1 hour. After the reaction, the temperature was lowered to 50°C and maintained. 1 part by weight of hydroxyethyl methacrylate was added to the insulated reactor, and the temperature was then raised to 70°C and the reaction was timed for 3 hours. After the reaction, the mixture was naturally cooled to room temperature to obtain a double-bond-terminated polyurethane prepolymer.
[0067] Preparation Example 12:
[0068] The preparation method of the double-bond terminated polyurethane prepolymer specifically includes the following steps:
[0069] After vacuum drying and dehydration of hexamethylene diisocyanate and polycaprolactone diol (number-average molecular weight of 2000), 9 parts by weight of the dried hexamethylene diisocyanate, 6.4 parts by weight of the dried polycaprolactone diol (number-average molecular weight of 2000), and 0.025 parts by weight of dibutyltin dilaurate were weighed and mixed in a reactor. Under nitrogen protection, the temperature was raised to 80°C and the reaction was timed for 1.5 hours. After the reaction, the temperature was lowered to 50°C and maintained. 2 parts by weight of hydroxyethyl methacrylate was added to the insulated reactor, and the temperature was then raised to 75°C and the reaction was timed for 3 hours. After the reaction, the mixture was naturally cooled to room temperature to obtain a double-bond-terminated polyurethane prepolymer.
[0070] Preparation Example 13:
[0071] The preparation method of the double-bond terminated polyurethane prepolymer specifically includes the following steps:
[0072] After vacuum drying and dehydration of hexamethylene diisocyanate and polycaprolactone diol (number-average molecular weight of 2000), 10 parts by weight of the dried hexamethylene diisocyanate, 6.8 parts by weight of the dried polycaprolactone diol (number-average molecular weight of 2000), and 0.035 parts by weight of dibutyltin dilaurate were weighed and mixed in a reactor. Under nitrogen protection, the temperature was raised to 85°C and the reaction was timed for 1.5 hours. After the reaction, the temperature was lowered to 60°C and maintained. 3 parts by weight of hydroxyethyl acrylate was added to the insulated reactor, and the temperature was then raised to 75°C and the reaction was timed for 3.5 hours. After the reaction, the mixture was naturally cooled to room temperature to obtain a double-bond-terminated polyurethane prepolymer.
[0073] Preparation Example 14:
[0074] The preparation method of the double-bond terminated polyurethane prepolymer specifically includes the following steps:
[0075] After vacuum drying and dehydration of hexamethylene diisocyanate and polycaprolactone diol (number-average molecular weight of 2000), 11 parts by weight of dried hexamethylene diisocyanate, 7 parts by weight of dried polycaprolactone diol (number-average molecular weight of 2000), and 0.04 parts by weight of dibutyltin dilaurate were weighed and mixed in a reactor. Under nitrogen protection, the temperature was raised to 90°C and the reaction was timed for 2 hours. After the reaction, the temperature was lowered to 60°C and maintained. 4 parts by weight of hydroxyethyl acrylate was added to the insulated reactor, and the temperature was then raised to 80°C and the reaction was timed for 4 hours. After the reaction, the mixture was naturally cooled to room temperature to obtain a double-bond-terminated polyurethane prepolymer.
[0076] Preparation Example 15:
[0077] The preparation method of the double-bond terminated polyurethane prepolymer specifically includes the following steps:
[0078] The hexamethylene diisocyanate in Preparation Example 14 was replaced by toluene diisocyanate, and the rest of the preparation process was consistent with Preparation Example 14.
[0079] Example 1:
[0080] A method for preparing a waterproof nylon fabric specifically comprises the following steps:
[0081] 3 parts by weight of a dicarboxylic acid mixture (prepared by mixing 1,4-benzenedicarboxylic acid, maleic acid, and anhydrous ethanol in a weight ratio of 1:3:8) and 1 part by weight of the modified diamine mixture obtained in Preparation Example 1 were mixed and stirred to disperse (sonication can be used to shorten the dispersion time and improve the dispersion effect) to obtain a mixed dispersion. The pH of the mixed dispersion was adjusted to 7.0 and then heated to 80°C for 90 minutes under reflux. After the reflux reaction, the reflux device was removed and the mixture was naturally cooled to room temperature to obtain a nylon salt solution. 2 parts by weight of the nylon salt solution and 0.016 parts by weight of antioxidant 1076 were added to a reactor. The reactor was closed and the air in the reactor was completely replaced with nitrogen. After the replacement, the reactor was heated to 200°C under nitrogen and the reaction time was set for 2 hours. After the reaction, the reactor was carefully vented to return to atmospheric pressure, then the discharged material was cooled to room temperature to obtain a nylon prepolymer. The resulting nylon prepolymer was placed in a vacuum drying oven and dried at 70°C for 6 hours. The dried nylon prepolymer was placed in a solid-phase polymerization kettle, which was then evacuated to 8 Pa and then heated to 230°C for 18 hours. After the reaction was completed, the mixture was naturally cooled to room temperature and removed from the kettle to obtain modified nylon. 5 parts by weight of the modified nylon and 2 parts by weight of the double-bond terminated polyurethane prepolymer obtained in Preparation Example 11 were added to an extruder, the extruder speed was set to 50 r / min, and the extruder was heated to 200°C and melt-blended at this temperature for 6 minutes. After the blending was completed, the slices obtained by extrusion were placed in a melt spinning device with a feed rate of 0.8 kg / h for spinning to obtain a waterproof nylon fabric.
[0082] Example 2:
[0083] A method for preparing a waterproof nylon fabric specifically comprises the following steps:
[0084] 3 parts by weight of a dicarboxylic acid mixture (prepared by mixing and dispersing 1,4-benzenedicarboxylic acid, maleic acid, and anhydrous ethanol in a weight ratio of 1:4:10) and 4 parts by weight of the modified diamine mixture obtained in Preparation Example 2 were mixed, stirred, and dispersed (sonication can be used to shorten the dispersion time and improve the dispersion effect) to obtain a mixed dispersion. The pH of the mixed dispersion was adjusted to 7.0, and then heated to 85°C for reflux reaction for 100 minutes. After the reflux reaction was completed, the reflux device was removed and the mixture was naturally cooled to room temperature to obtain a nylon salt solution. 2 parts by weight of the nylon salt solution and 0.017 parts by weight of antioxidant 1076 were added to a reactor. The reactor was closed and the air in the reactor was completely replaced with nitrogen. After the replacement was completed, the reactor was heated to 210°C under nitrogen protection and the reaction was timed for 2.5 hours. After the reaction, the reactor was carefully vented to atmospheric pressure, and the resulting mixture was cooled to room temperature to obtain a nylon prepolymer. The resulting nylon prepolymer was placed in a vacuum drying oven and dried at 75°C for 8 hours. The dried nylon prepolymer was placed in a solid-phase polymerization kettle, which was then evacuated to 8 Pa and then heated to 235°C for 19 hours. After the reaction, the mixture was naturally cooled to room temperature and removed from the kettle to obtain a modified nylon. 6 parts by weight of the modified nylon and 2.5 parts by weight of the double-bond-terminated polyurethane prepolymer obtained in Preparation Example 12 were added to an extruder at a speed of 60 rpm. The extruder was then heated to 200°C and melt-blended at this temperature for 7 minutes. After the blending, the extruded chips were placed in a melt spinning apparatus at a feed rate of 0.8 kg / h to produce a waterproof nylon fabric.
[0085] Example 3:
[0086] A method for preparing a waterproof nylon fabric specifically comprises the following steps:
[0087] 3 parts by weight of a dicarboxylic acid mixture (prepared by mixing and dispersing 1,4-benzenedioic acid, maleic acid, and anhydrous ethanol in a weight ratio of 1:4:12) and 5 parts by weight of the modified diamine mixture obtained in Preparation Example 3 were mixed, stirred, and dispersed (sonication can be used to shorten the dispersion time and improve the dispersion effect) to obtain a mixed dispersion. The pH of the mixed dispersion was adjusted to 7.5, and then heated to 85°C for reflux reaction for 110 minutes. After the reflux reaction was completed, the reflux device was removed and the mixture was naturally cooled to room temperature to obtain a nylon salt solution. 2 parts by weight of the nylon salt solution and 0.018 parts by weight of antioxidant 246 were added to a reactor. The reactor was closed and the air in the reactor was completely replaced with nitrogen. After the replacement was completed, the reactor was heated to 220°C under nitrogen protection and the reaction was timed for 2.5 hours. After the reaction, the reactor was carefully vented to atmospheric pressure, and the resulting mixture was cooled to room temperature to obtain a nylon prepolymer. The resulting nylon prepolymer was placed in a vacuum drying oven and dried at 75°C for 10 hours. The dried nylon prepolymer was placed in a solid-phase polymerization reactor, which was then evacuated to 9 Pa and then heated to 235°C for 20 hours. After the reaction, the mixture was naturally cooled to room temperature and removed from the reactor to obtain a modified nylon. 7 parts by weight of the modified nylon and 2.5 parts by weight of the double-bond-terminated polyurethane prepolymer obtained in Preparation Example 13 were added to an extruder at a speed of 70 rpm. The extruder was then heated to 210°C and melt-blended at this temperature for 8 minutes. After the extrusion, the resulting chips were placed in a melt spinning apparatus at a feed rate of 0.8 kg / h to produce a waterproof nylon fabric.
[0088] Example 4:
[0089] A method for preparing a waterproof nylon fabric specifically comprises the following steps:
[0090] 3 parts by weight of a dicarboxylic acid mixture (prepared by mixing and dispersing 1,4-benzenedioic acid, maleic acid, and anhydrous ethanol in a weight ratio of 1:5:12) and 6 parts by weight of the modified diamine mixture obtained in Preparation Example 4 were mixed and stirred (sonication can be used to shorten the dispersion time and improve the dispersion effect) to obtain a mixed dispersion. The pH of the mixed dispersion was adjusted to 7.5 and then heated to 90°C for 110 minutes under reflux. After the reflux reaction, the reflux device was removed and the mixture was naturally cooled to room temperature to obtain a nylon salt solution. 2 parts by weight of the nylon salt solution and 0.02 parts by weight of antioxidant 264 were added to a reactor. The reactor was closed and the air in the reactor was completely replaced with nitrogen. After the replacement, the reactor was heated to 220°C under nitrogen protection and the reaction time was set for 3 hours. After the reaction, the reactor was carefully vented to return to atmospheric pressure, and the discharged material was cooled to room temperature to obtain a nylon prepolymer. The resulting nylon prepolymer was placed in a vacuum drying oven and dried at 80°C for 10 hours. The dried nylon prepolymer was placed in a solid-phase polymerization kettle, which was then evacuated to 10 Pa and then heated to 240°C for 20 hours. After the reaction was completed, the mixture was naturally cooled to room temperature and removed from the kettle to obtain modified nylon. 8 parts by weight of the modified nylon and 3 parts by weight of the double-bond terminated polyurethane prepolymer obtained in Preparation Example 14 were added to an extruder, the extruder speed was set to 80 r / min, and the extruder was heated to 210°C and melt-blended at this temperature for 9 minutes. After the blending was completed, the slices obtained by extrusion were placed in a melt spinning device with a feed rate of 0.8 kg / h for spinning to obtain a waterproof nylon fabric.
[0091] Comparative Example 1:
[0092] A method for preparing a waterproof nylon fabric specifically comprises the following steps:
[0093] The modified diamine mixed solution in Example 4 was replaced by the modified diamine mixed solution obtained in Preparation Example 5, and the rest of the preparation process was consistent with that in Example 4.
[0094] Comparative Example 2:
[0095] A method for preparing a waterproof nylon fabric specifically comprises the following steps:
[0096] The modified diamine mixed solution in Example 4 was replaced by the modified diamine mixed solution obtained in Preparation Example 6, and the rest of the preparation process was consistent with that in Example 4.
[0097] Comparative Example 3:
[0098] A method for preparing a waterproof nylon fabric specifically comprises the following steps:
[0099] The modified diamine mixed solution in Example 4 was replaced by the modified diamine mixed solution obtained in Preparation Example 7, and the rest of the preparation process was consistent with that in Example 4.
[0100] Comparative Example 4:
[0101] A method for preparing a waterproof nylon fabric specifically comprises the following steps:
[0102] The modified diamine mixed solution in Example 4 was replaced by the modified diamine mixed solution obtained in Preparation Example 8, and the rest of the preparation process was consistent with that in Example 4.
[0103] Comparative Example 5:
[0104] A method for preparing a waterproof nylon fabric specifically comprises the following steps:
[0105] The modified diamine mixed solution in Example 4 was replaced by the modified diamine mixed solution obtained in Preparation Example 9, and the rest of the preparation process was consistent with that in Example 4.
[0106] Comparative Example 6:
[0107] A method for preparing a waterproof nylon fabric specifically comprises the following steps:
[0108] The modified diamine mixed solution in Example 4 was replaced by the modified diamine mixed solution obtained in Preparation Example 10, and the rest of the preparation process was consistent with that in Example 4.
[0109] Comparative Example 7:
[0110] A method for preparing a waterproof nylon fabric specifically comprises the following steps:
[0111] The double-bond terminated polyurethane prepolymer in Example 4 was replaced by the double-bond terminated polyurethane prepolymer obtained in Preparation Example 15, and the rest of the preparation process was consistent with Example 4.
[0112] Comparative Example 8:
[0113] A method for preparing a waterproof nylon fabric specifically comprises the following steps:
[0114] The dicarboxylic acid mixture in Example 4 (obtained by mixing and dispersing 1,4-benzenedioic acid, maleic acid and anhydrous ethanol in a weight ratio of 1:5:12) was replaced by a dicarboxylic acid mixture (obtained by mixing and dispersing maleic acid and anhydrous ethanol in a weight ratio of 6:12). The rest of the preparation process was consistent with that of Example 4.
[0115] Comparative Example 9:
[0116] A method for preparing a waterproof nylon fabric specifically comprises the following steps:
[0117] The dicarboxylic acid mixture in Example 4 (obtained by mixing and dispersing 1,4-benzenedioic acid, maleic acid and anhydrous ethanol in a weight ratio of 1:5:12) was replaced by a dicarboxylic acid mixture (obtained by mixing and dispersing 1,4-benzenedioic acid and anhydrous ethanol in a weight ratio of 6:12). The rest of the preparation process was consistent with Example 4.
[0118] The waterproof nylon fabrics obtained in Examples 1 to 4 and Comparative Examples 1 to 9 were tested for their waterproof grades according to AATCC 22-2017 Water Repellency: Spray Test. The results are shown in Table 1 below.
[0119] Table 1 Waterproof grade
[0120] Sources Waterproof grade Example 1 90 Example 2 90 Example 3 100 Example 4 90 Comparative Example 1 80 Comparative Example 2 50 Comparative Example 3 90 Comparative Example 4 50 Comparative Example 5 50 Comparative Example 6 0 Comparative Example 7 0 Comparative Example 8 0 Comparative Example 9 0
[0121] The waterproof nylon fabrics obtained in Examples 1 to 4 and Comparative Examples 1 to 9 were washed with commercially available laundry detergent. The amount of laundry detergent used was 2 g per liter of water. The water temperature was 40°C. After rubbing for 5 minutes, rinsing with clean water and dehydrating, one wash was considered. After washing 30 times, the waterproof grade was tested according to "AATCC 22-2017 Water Repellency: Spray Test". The results are shown in Table 2 below.
[0122] Table 2 Waterproof grade after 30 washes
[0123] Sources Waterproof grade Example 1 80 Example 2 80 Example 3 100 Example 4 80 Comparative Example 1 50 Comparative Example 2 0 Comparative Example 3 70 Comparative Example 4 0 Comparative Example 5 0 Comparative Example 6 0 Comparative Example 7 0 Comparative Example 8 0 Comparative Example 9 0
[0124] According to GB / T 5453-1997 Determination of Air Permeability of Textile Fabrics, the air permeability of the waterproof nylon fabrics obtained in Examples 1 to 4 and Comparative Examples 1 to 9 was measured. The test area was 20 cm 2 , the pressure drop is 100Pa, and the air permeability is measured. The results are shown in Table 3 below.
[0125] Table 3 Air permeability
[0126] Sources Air permeability (mm / s) Example 1 159.8 Example 2 161.7 Example 3 163.1 Example 4 162.9 Comparative Example 1 70.6 Comparative Example 2 62.8 Comparative Example 3 91.7 Comparative Example 4 84.5 Comparative Example 5 302.4 Comparative Example 6 278.1 Comparative Example 7 81.7 Comparative Example 8 261.9 Comparative Example 9 286.5
[0127] According to GB / T 3923.1-2013 Tensile properties of textile fabrics Part 1, the mechanical properties of the waterproof nylon fabrics obtained in Examples 1 to 4 and Comparative Examples 1 to 9 were tested. The results are shown in Table 4 below.
[0128] Table 4 Mechanical properties
[0129]
[0130]
[0131] The following conclusions can be drawn from Tables 1 to 4 above:
[0132] (1) It can be found from Examples 1 to 4 that the waterproof nylon fabric modified by the present invention not only has good waterproof performance and breathable performance, but also has good washable waterproof performance and mechanical properties.
[0133] (2) It can be found from Comparative Example 1 that although the waterproof performance of the prepared waterproof nylon fabric is good, its air permeability and mechanical properties are poor. This may be because although 3-aminopropyltrimethoxysilane has an amino group, the carbon chain in 3-aminopropyltrimethoxysilane is too short, and the polymerization cross-linking may be too dense, which not only affects the air permeability, but also the excessive cross-linking density easily leads to increased brittleness, thereby reducing the tensile strength, which is not conducive to the use of waterproof nylon fabrics.
[0134] (3) Comparative Example 2 shows that the waterproof nylon fabric prepared has poor waterproof performance, air permeability and mechanical properties. This may be because although the silane coupling agent KH-560 can introduce a terminal hydroxyl aldehyde compound through hydrolysis and condensation and then react with a diamine compound to obtain a modified diamine, the silane coupling agent KH-560 does not contain an amino group. When reacting with the diamine compound, one amino group of the diamine is consumed, resulting in a lack of amino groups and inability to extend the chain polymerization, which may affect the polymerization of the modified diamine and dicarboxylic acid to prepare nylon, thereby causing the performance of the waterproof nylon fabric to deteriorate.
[0135] (4) Comparative Example 3 shows that although the waterproof performance of the prepared waterproof nylon fabric is good, its air permeability and mechanical properties are poor. This may be because the carbon chain of glyceraldehyde is shorter than that of hydroxycitronellal, and the polymerization cross-linking may be too dense, which not only affects the air permeability, but also the excessive cross-linking density easily leads to increased brittleness, thereby reducing the tensile strength, which is not conducive to the use of waterproof nylon fabrics.
[0136] (5) Comparative Example 4 shows that the waterproof performance, air permeability and mechanical properties of the prepared waterproof nylon fabric are relatively poor. This may be because although adipic acid can form a siloxane bond through the condensation of carboxyl and silanol groups, it lacks the high-temperature resistant imine bond formed with the diamine compound. It only relies on the steric hindrance effect of the benzene ring, which may result in poor cross-linking effect during high-temperature cross-linking and more severe breakage, thereby weakening the performance of the waterproof nylon fabric.
[0137] (6) Comparative Examples 5 and 6 show that the waterproof and mechanical properties of the prepared waterproof nylon fabrics are relatively poor. This may be because although both 1,3-propylenediamine and 1,10-decanediamine have diamino groups and can participate in the reaction of preparing nylon, the carbon chains of the diamine compounds are too long or too short in the polymerization reaction of this system, which, on the one hand, leads to poor crosslinking effect of high-temperature crosslinking, and on the other hand, may make the interface bonding between the modified nylon and the double-bond terminated polyurethane prepolymer poor, which may cause the final prepared waterproof nylon fabric to be severely damaged, thereby weakening the performance of the waterproof nylon fabric.
[0138] (7) It can be found from Comparative Example 7 that the waterproof performance, air permeability and mechanical properties of the prepared waterproof nylon fabric are relatively poor. This may be because toluene diisocyanate contains a benzene ring structure compared to hexamethylene diisocyanate. In this system, since a dicarboxylic acid containing a benzene ring structure is introduced into the system for preparing modified nylon, if the benzene ring content in the double-bond terminated polyurethane prepolymer is further increased, although the rigid structure of the benzene ring helps to improve the hydrophobicity and high temperature resistance, too many benzene rings may easily lead to excessive brittleness of the mixture during high-temperature cross-linking, thereby causing the performance of the waterproof nylon fabric finally prepared to deteriorate.
[0139] (8) It can be found from Comparative Example 8 that the waterproof and mechanical properties of the prepared waterproof nylon fabric are relatively poor. This may be because the dicarboxylic acid mixture lacks 1,4-benzenedioic acid containing a benzene ring structure, which is the main structure of nylon. As a result, the high-temperature resistance performance relies solely on the imine bond. Under the high temperature during melt blending, the steric hindrance of the benzene ring is lost, and the imine bond may be severely damaged, affecting the cross-linking effect of the melt blending. As a result, the waterproof nylon fabric finally prepared is severely damaged, which in turn weakens the performance of the waterproof nylon fabric.
[0140] (9) Comparative Example 9 shows that the waterproof performance, air permeability and mechanical properties of the prepared waterproof nylon fabric are relatively poor. This may be due to the lack of maleic acid containing a double bond structure in the dicarboxylic acid mixture, which may lead to poor interfacial bonding compatibility between the prepared modified nylon and the double-bond terminated polyurethane prepolymer, affecting the cross-linking effect of melt blending, and thus causing the final prepared waterproof nylon fabric to be severely damaged and its performance to decline.
[0141] The embodiments described above provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention, and such changes and modifications fall within the scope of the present invention as claimed.
Claims
1. A method for preparing a waterproof nylon fabric, characterized in that: The preparation method comprises the following steps: The dicarboxylic acid mixture and the modified diamine mixture are mixed and dispersed in a weight ratio of 1:1-2, and the pH is adjusted to 7.0-7.5, and then heated to 80-90°C for a reaction time of 90-110 minutes to obtain a nylon salt solution; The nylon salt solution and the antioxidant are mixed in a weight ratio of 1:0.008-0.01, and the mixture is heated to 200° C.-220° C. under nitrogen atmosphere and reacted for 2 h-3 h to obtain a nylon prepolymer; The nylon prepolymer is dried at 70°C to 80°C for 6h to 10h, then vacuumed to 8Pa to 10Pa, and then heated to 230°C to 240°C for 18h to 20h to obtain modified nylon; The modified nylon and the double-bond terminated polyurethane prepolymer are mixed in an extruder in a weight ratio of 5-8:2-3, and are melt-blended at a speed of 50-80 r / min and a temperature of 200-210° C. for 6-9 minutes to obtain a waterproof nylon fabric.
2. The method for preparing a waterproof nylon fabric according to claim 1, characterized in that: The dicarboxylic acid mixture consists of a benzene ring-containing dicarboxylic acid, an olefin dicarboxylic acid and anhydrous ethanol in a weight ratio of 1:3-5:8-12.
3. The method for preparing a waterproof nylon fabric according to claim 1, characterized in that: The preparation method of the modified diamine mixed solution comprises the following steps: A silane coupling agent, a terminal hydroxyl aldehyde compound and a mixed solvent are mixed in a weight ratio of 1:3 to 6:10 to 20, and the pH is adjusted to 4 to 4.
5. The mixture is then heated to 60° C. to 70° C. and reacted for 2 to 3 hours to obtain a modified silane coupling agent. The modified silane coupling agent and the diamine compound are mixed in a weight ratio of 1:2-3, and then stirred and reacted in an environment of 25-30° C. for 12-15 hours to obtain a modified diamine mixed solution.
4. The method for preparing a waterproof nylon fabric according to claim 3, characterized in that: The silane coupling agent includes silane coupling agent KH-792.
5. The method for preparing a waterproof nylon fabric according to claim 3, characterized in that: The terminal hydroxy aldehyde compound includes hydroxycitronellal.
6. The method for preparing a waterproof nylon fabric according to claim 3, characterized in that: The diamine compound includes 1,5-pentanediamine or 1,6-hexanediamine.
7. The method for preparing a waterproof nylon fabric according to claim 1, characterized in that: The preparation method of the double-bond terminated polyurethane prepolymer comprises the following steps: Hexamethylene diisocyanate, polycaprolactone diol and dibutyltin dilaurate are mixed and heated to 80°C to 90°C for reaction for 1h to 2h, then cooled to 50°C to 60°C and a hydroxyl compound containing a double bond is added, and the mixture is heated to 70°C to 80°C and reacted for 3h to 4h to obtain a double-bond terminated polyurethane prepolymer.
8. The method for preparing a waterproof nylon fabric according to claim 7, characterized in that: The double bond hydroxy compound includes hydroxyethyl methacrylate or hydroxyethyl acrylate.
9. The method for preparing a waterproof nylon fabric according to claim 7, characterized in that: The weight ratio of the hexamethylene diisocyanate: polycaprolactone diol: dibutyltin dilaurate: hydroxy compound containing a double bond is 8-11: 6-7: 0.015-0.04: 1-4.
10. A waterproof nylon fabric prepared by the method for preparing a waterproof nylon fabric according to any one of claims 1 to 9.
Citation Information
Patent Citations
Low-moisture-absorption nylon material and preparation method thereof
CN117551344A
Cited By
Preparation method of composite nylon material
CN122103887A